2004
DOI: 10.1080/10428190410001667712
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Adjuvant Radiotherapy in Stage IV Diffuse Large Cell Lymphoma Improve Outcome

Abstract: The role of adjuvant radiotherapy to sites of nodal bulky disease in patients with aggressive diffuse large cell lymphoma (DLCL), and stage IV remain undefined. We began a prospective controlled clinical trial to evaluate impact in event free survival (EFS) and overall survival (OS) in a large cohort of patients with a longer follow-up. Between 1989 and 1995; 341 patients with aggressive DLCL and presence of nodal bulky disease (tumor mass > 10 cm) in pathological proven complete response after intensive chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 17 publications
0
28
0
1
Order By: Relevance
“…Although historical comparative trials suggested a possible benefit, [86][87][88] recent improvement in systemic therapy may have diminished its role. To date, there have been no randomized trials evaluating the role of consolidative radiation therapy in DLBCL in the rituximab era.…”
Section: Consolidative Radiation Therapy and Role Of Pet Scanningmentioning
confidence: 99%
“…Although historical comparative trials suggested a possible benefit, [86][87][88] recent improvement in systemic therapy may have diminished its role. To date, there have been no randomized trials evaluating the role of consolidative radiation therapy in DLBCL in the rituximab era.…”
Section: Consolidative Radiation Therapy and Role Of Pet Scanningmentioning
confidence: 99%
“…Natomiast rola radioterapii jest marginalna. Wpływ napromieniania zmian resztkowych po leczeniu systemowym bez rytuksymabu u chorych z guzami > 10 cm oceniono w kilku prospektywnych i retrospektywnych badaniach [29][30][31][32][33], a po leczeniu R-CHOP w trzech retrospektywnych badaniach z MDACC i Duke University oraz Emory University [34][35][36]. We wszystkich wykazano korzyść z radioterapii w odniesieniu do pięcioletniej kontroli miejscowej, czasu do progresji, a także w odniesieniu do ogólnego czasu przeżycia.…”
Section: Dlbcl W Stopniu III I Ivunclassified
“…Researchers focus on supplemental treatment such as radiation therapy (RT). In the prerituximab era, several studies found a recurrence in 52-65% of patients who had achieved an initial complete response (CR) to chemotherapy alone, while consolidation RT after CHOP chemotherapy could decrease the risk of disease recurrence and improve the outcome of patients with stage I-IV DLBCL [2,3,4,5]. …”
Section: Introductionmentioning
confidence: 99%